2020
DOI: 10.3390/biom10111578
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Connexin43 Channels as Candidate Targets in Epilepsy Treatment

Abstract: In epilepsy research, emphasis is put on exploring non-neuronal targets such as astrocytic proteins, since many patients remain pharmacoresistant to current treatments, which almost all target neuronal mechanisms. This paper reviews available data on astrocytic connexin43 (Cx43) signaling in seizures and epilepsy. Cx43 is a widely expressed transmembrane protein and the constituent of gap junctions (GJs) and hemichannels (HCs), allowing intercellular and extracellular communication, respectively. A plethora of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 214 publications
0
30
0
Order By: Relevance
“…It has been well established the higher vigilance for seizure is warranted during treatment with CLZ and QTP [ 77 , 78 ]. Recently, preclinical findings using several epileptic/convulsive animal models have displayed the possibility that upregulation/hyperfunction of Cx43 contributes to development of epileptogenesis/ictogenesis [ 2 , 10 , 11 , 12 , 22 , 79 , 80 , 81 , 82 ]. Furthermore, pharmacodynamic studies reported that Cx43 is one of the major targets of several anti-seizure agents, zonisamide, lacosamide, brivaracetam and VPA [ 8 , 9 , 11 , 12 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established the higher vigilance for seizure is warranted during treatment with CLZ and QTP [ 77 , 78 ]. Recently, preclinical findings using several epileptic/convulsive animal models have displayed the possibility that upregulation/hyperfunction of Cx43 contributes to development of epileptogenesis/ictogenesis [ 2 , 10 , 11 , 12 , 22 , 79 , 80 , 81 , 82 ]. Furthermore, pharmacodynamic studies reported that Cx43 is one of the major targets of several anti-seizure agents, zonisamide, lacosamide, brivaracetam and VPA [ 8 , 9 , 11 , 12 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharmacodynamic studies reported that Cx43 is one of the major targets of several anti-seizure agents, zonisamide, lacosamide, brivaracetam and VPA [ 8 , 9 , 11 , 12 , 67 ]. Astroglial hemichannel is activated by depolarization and exposure to transient toxic (100 mM) or persistent pathological (10 mM) extracellular K + , and active state of hemichannel continues several hours [ 8 , 9 , 10 , 11 , 12 , 22 , 67 , 79 ]. Therefore, the stimulatory effects of CLZ and QTP on astroglial Cx43 containing hemichannel activity seem to be rational mechanisms regarding the adverse seizure reaction induced by CLZ and QTP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a nonselective connexin inhibitor, CBX, and Cx43-selective mimetic peptide inhibitors Gap27 and Gap26, induced depression, anhedonia, and anxiety-like behaviour [ 59 ]. These three connexin inhibitors, CBX, Gap26, and Gap27, inhibit both astroglial Cx43-containing gap junction and hemichannel [ 134 ]. However, lacosamide, which inhibits astroglial hemichannel activity without affecting Cx43 synthesis, led to a mild but antidepressant-like effect rather than depressive mood induction [ 116 , 117 , 118 ].…”
Section: Candidate Pathophysiology Of Mood Disorders Associated Wimentioning
confidence: 99%
“…In addition, spatial potassium buffering is known to be linked to glutamate uptake via glutamate transporters [e.g., excitatory amino acid transporters 1 (EAAT1) and EAAT2] and water transport via aquaporin-4 (AQP4) by astrocytes (26)(27)(28)(29)(30)(31). Moreover, both connexin30 and connexin43 in astrocytic gap junctions were shown to play a critical role in normal K + redistribution, using double knockout techniques in mice (32,33).…”
Section: Spatial Potassium Buffering and Astrocytic Kir41 Channelsmentioning
confidence: 99%